Meta-Analysis of Teams Games Tournament Learning Model on Mathematics Learning Outcomes - Muhammad Aris Ariful Wafa; Elvira Hoesein Radia (Universitas Pendidikan Ganesha, 2020)
This study aims to analyze the use of the teams games tournament model in improving the math learning outcomes of elementary school students. This research uses the meta-analysis method. This research was conducted by formulating research problems, tracing relevant research results for analysis. Data collection is done by searching for online journals using Google Scholar. Search results obtained 10 articles of research data sources. The analysis used a comparison method to determine the impact of implementing the Teams Games Tournament learning model in improving math learning outcomes. Based on the analysis results of the Teams Games Tournament model was able to improve students' math learning results ranging from the lowest 16.8% to the highest score of 102.9% with an average of 32.59%. So, the TGT model has a positive impact on the learning outcomes of elementary school students.